Faktor-Faktor Penghambat Penyelesaian Tugas Akhir Skripsi (Studi Kasus Pada Mahasiswa Akuntansi Angkatan 2018 UPN “Veteran” Jawa Timur) - Amaria Purba, Dinda; Munari , Munari (Jurnal Syntax Fusion, 2023)
The thesis final project is a scientific work that must be made by final-year students to obtain an academic degree. But in reality, there are still many students who need help in doing the final thesis. This study aims to see and test how psychological well-being, academic ability, thesis administration system, and lecturer guidance influence the completion of the final thesis assignment for accounting students class of 2018 UPN "Veteran" Jawa Timur. The population in this study numbered 222 accounting students class of the 2018 UPN "Veteran" Jawa Timur who was working on or had completed their final thesis assignment. The sampling technique used is technique purposive sampling. This research uses quantitative methods. The analytical method used isPartial Least Square (PLS) with the help of software WrapPLS 7.0. The results showed that psychological well-being and lecturer guidance had no effect on completing the thesis's final assignment. In contrast, academic ability and thesis administration system affect the completion of the thesis final assignment.